The Current Significance of Liquidity Preference - Wallich, H. C. (Quarterly Journal of Economics, 1946)
Introduction, 490. — I. General comments, 491. — II. Application to equity assets, 494. — III. Components of the money supply, 497. — Trust funds and financial corporations, 502. — Personal holdings, 502. — Nonfinancial corporations and unincorporated businesses, 503. — Commercial banks, 604. — Market behavior, 505. — IV. Conclusion: the future of idle balances, 507.